2008
DOI: 10.1038/sj.ki.5002771
|View full text |Cite
|
Sign up to set email alerts
|

Tracking kidney volume in mice with polycystic kidney disease by magnetic resonance imaging

Abstract: Polycystic kidney disease is characterized by the progressive enlargement of kidneys due to expanding fluid-filled cysts with the rate of renal volume increase held to be a marker of disease progression. Magnetic resonance imaging (MRI) is used to monitor changes in renal volume in patients with polycystic kidney disease; however, it has not been effectively used in mice to monitor changes in kidney volume during drug treatment studies. We used a powerful 9.4-T horizontal bore magnetic resonance scanner to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 11 publications
3
38
0
Order By: Relevance
“…Magnetic resonance imaging has been shown to be a more sensitive biomarker of disease progression than either serum creatinine or estimated GFR. Magnetic resonance imaging is already being used as a surrogate outcome to increases in creatinine in clinical trials (42,43). It is thought that if we can intervene before the rise in serum creatinine, therapies can have a greater chance of success.…”
Section: Polycystic Kidney Diseasementioning
confidence: 99%
“…Magnetic resonance imaging has been shown to be a more sensitive biomarker of disease progression than either serum creatinine or estimated GFR. Magnetic resonance imaging is already being used as a surrogate outcome to increases in creatinine in clinical trials (42,43). It is thought that if we can intervene before the rise in serum creatinine, therapies can have a greater chance of success.…”
Section: Polycystic Kidney Diseasementioning
confidence: 99%
“…9 In addition, Almajdub et al 10 regards mouse kidney phenotyping is as being an important issue, and in vivo imaging allows for longitudinal studies. Therefore, micro-CT appears to be a suitable method for phenotyping the kidney anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…9,14 Another study compared the efficacy of contrast-enhanced micro-CT and MRI in animal models. The authors concluded that, in addition to the advantages of not exposing the animal to ionizing radiation, MRI provides a more complete assessment.…”
mentioning
confidence: 99%
“…Imaging modalities such as ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI) are used to monitor disease progression (8). Clinical studies utilize total kidney volume (TKV) measured by MRI as an image-based biomarker to follow the progression of ADPKD since larger TKVs have been shown to correlate with worse prognosis in ADPKD in both human (9), and murine studies (10). However, there are challenges with using TKV as a marker of disease progression.…”
Section: Introductionmentioning
confidence: 99%